2019
DOI: 10.1038/s41377-019-0206-2
|View full text |Cite
|
Sign up to set email alerts
|

Full-colour nanoprint-hologram synchronous metasurface with arbitrary hue-saturation-brightness control

Abstract: The colour gamut, a two-dimensional (2D) colour space primarily comprising hue and saturation (HS), lays the most important foundation for the colour display and printing industries. Recently, the metasurface has been considered a promising paradigm for nanoprinting and holographic imaging, demonstrating a subwavelength image resolution, a flat profile, high durability, and multi-functionalities. Much effort has been devoted to broaden the 2D HS plane, also known as the CIE map. However, the brightness (B), as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
139
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(147 citation statements)
references
References 37 publications
(22 reference statements)
1
139
0
Order By: Relevance
“…In [169], it has been demonstrated that with two-step (on and off) amplitude manipulation it is possible to reduce speckle noise, an intrinsic problem of phase-only holograms. By combining a color filter and a meta-hologram, meta-hologram with microprint functionality is presented [177][178][179]. Particularly, in [177], a color filter and meta-hologram are realized on a single metamaterial.…”
Section: Full-color Meta-hologramsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [169], it has been demonstrated that with two-step (on and off) amplitude manipulation it is possible to reduce speckle noise, an intrinsic problem of phase-only holograms. By combining a color filter and a meta-hologram, meta-hologram with microprint functionality is presented [177][178][179]. Particularly, in [177], a color filter and meta-hologram are realized on a single metamaterial.…”
Section: Full-color Meta-hologramsmentioning
confidence: 99%
“…By combining a color filter and a meta-hologram, meta-hologram with microprint functionality is presented [177][178][179]. Particularly, in [177], a color filter and meta-hologram are realized on a single metamaterial. While most studies have assumed either the reflection mode or the transmission mode of operation, in [170], a meta-hologram that simultaneously generates different images on the reflection and transmission sides has also been proposed.…”
Section: Full-color Meta-hologramsmentioning
confidence: 99%
“…In addition, most of the reported multiwavelength metadevices only work at two wavelengths due to the strong coupling effect for closely spaced resonators. Up to now, very few 2-bit tri-wavelength and quad-wavelength metallic metadevices at reflection mode with the linear polarization [31][32][33] and tri-wavelength dielectric metadevices at transmission mode with the circular polarization [34][35][36] have been demonstrated. Compared to the propagation phase modulation (usually for linear polarization), the metasurface based on geometric phase modulation (for circular polarization) is favored, where 2 phase modulation could be continuously achieved by rotating the resonator instead of tuning the geometric size of the resonator.…”
Section: Doi: 101002/adts202000099mentioning
confidence: 99%
“…However, with this approach the information density of each metasurface is not increased at all. Adjusting the complex transmission coefficients of metasurfaces is another feasible way for merging holography and nanoprinting, which is realized by utilizing the coupling between two nanostructures [ 28 ] or optimizing the dimensions of nanostructures so they can act as wave‐plates with different phase delays. [ 29 ] In these schemes, the amplitude distribution of transmitted light, which is determined by the grayscale of nanoprinting pattern, limits the diffraction efficiency of holographic image.…”
Section: Introductionmentioning
confidence: 99%